PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DI RESTORAN CARLS JR GRAN RUBINA - Aditya Mahdi Farsya; Wasino (Panorama Nusantara, 2021)
This research was conducted at Carls JR Gran Rubina customers. The purpose of this study was to determine the impact of product quality and price perception on customer satisfaction at Carls JR Gran Rubina. Data used in this study are primary data obtained from 100 respondents from Carls JR Gran Rubina customers with a purposive sampling method. The analytical method used is quantitative analysis with multiple regression analysis. This analysis includes: validity and reliability, the classic assumption test, multiple regression analysis, reviewing hypotheses with the t test and F test, and the coefficient of determination (R2). The variable price perception has the greatest influence on customer satisfaction by 0.546 received by along with the product quality variable by 0.319. Hypothesis testing uses t test which shows the independent variables namely product quality (X1) and price perception (X2) which are investigated partially and significantly affect customer satisfaction variables (Y). Then through the F test it can be seen that the variable product quality and perceived price requirements for customer satisfaction depend. Adjusted R Square explains that the numbers 79.56% satisfaction variable can be accepted by two independent variables in the multiple linear regression equation. While the remaining 20.44% was approved by other variables beyond the two variables used in this study.